Increasing Knowledge, Self-Efficacy and Hemoglobin Levels in Pre-Conception Women through Nutrition Assistance Program - Rosdianah Rosdianah; Nurjannah Bachri; Qonita Kurnia Anjani; Karolus Wangi; Jumrah Sudirman; Abdul Malik Iskandar (Al-Sihah : The Public Health Science Journal, 2023)
Anemia, which is associated with various complications during pregnancy and childbirth can be prevented, especially in pre-conception or pre-pregnancy women, by fulfilling nutrition needs. One way to achieve this is by implementing nutrition assistance programs specifically designed for pregnant women or those planning to conceive. Therefore, this study aims to examine the impact of a dietary support program on the knowledge, self-efficacy, and hemoglobin level of pre-conception women. The design used was a non-randomized controlled trial with a pretest-posttest approach, while the sample consisted of married women preparing to get pregnant, with a total of 67 people meeting the inclusion criteria. Data obtained were analyzed using the Wilcoxon Signed Ranks Test and Independent sample T-test. The results demonstrated a significant difference in knowledge levels (p=0.000), self-efficacy (p=0.000), and hemoglobin levels (p=0.000) between the intervention and control groups. Therefore, it is essential to address the readiness of pre-conception women, particularly regarding their nutrition status, to prevent potential complications that may arise during pregnancy and childbirth.